BCAS3 exhibits oncogenic properties by promoting CRL4A‐mediated ubiquitination of p53 in breast cancer. (9th July 2021) - Zhou, Zhe; Qiu, Rongfang; Liu, Wei; Yang, Tianshu; Li, Gen; Huang, Wei; Teng, Xu; Yang, Yunkai; Yu, Hefen; Yang, Yang; Wang, Yan
Abstract: Objectives: Breast cancer‐amplified sequence 3 (BCAS3) was initially found to be amplified in human breast cancer (BRCA); however, there has been little consensus on the functions of BCAS3 in breast tumours. Materials and methods: We analysed BCAS3 expression in BRCA using bio‐information tools. Affinity purification and mass spectrometry were employed to identify BCAS3‐associated proteins. GST pull‐down and ubiquitination assays were performed to analyse the interaction mechanism between BCAS3/p53 and CUL4A‐RING E3 ubiquitin ligase (CRL4A) complex. BCAS3 was knocked down individually or in combination with p53 in MCF‐7 cells to further explore the biological functions of the BCAS3/p53 axis. The clinical values of BCAS3 for BRCA progression were evaluated via semiquantitative immunohistochemistry (IHC) analysis and Cox regression. Results: We reported that the expression level of BCAS3 in BRCA was higher than that in adjacent normal tissues. High BCAS3 expression promoted growth, inhibited apoptosis and conferred chemoresistance in breast cancer cells. Mechanistically, BCAS3 overexpression fostered BRCA cell growth by interacting with the CRL4A complex and promoting ubiquitination and proteasomal degradation of p53. Furthermore, BCAS3 could regulate cell growth, apoptosis and chemoresistance through a p53‐mediated mechanism. Clinically, BCAS3 overexpression was significantly correlated with a malignant phenotype. Moreover, higher expression of BCAS3 correlates with shorter overall survival (OS) in BRCA. Conclusions: The functional characterization of BCAS3 offers new insights into the oncogenic properties and chemotherapy resistance in breast cancer. Abstract : BCAS3, the WD40 repeat protein, is a new interaction partner of CUL4A‐RING E3 ubiquitin ligase (CRL4A) complex. The cullin subunit of CUL4A acts as a scaffold and is responsible for ROC1 connection to recruit E2, while the other end recruits p53 for ubiquitination degradation through BCAS3 which directly binds to DDB1. The biological process of ubiquitination p53 by BCAS3/CRL4A complex is involved in regulating cell proliferation, apoptosis and chemotherapy resistance in breast cancer.